Synchronous or Asynchronous: Students’ Perceptions And Learning Outcomes In Teaching English For Young Learners (TEYL) Courses - Yuli Astutik; Fika Megawati; Noly Shofiyah; Vidya Mandarani; Saltanat Meiramova; Pasya Rahma Tamara (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background: Despite the growing adoption of online learning, limited research has examined how synchronous and asynchronous modalities affect pre-service teachers’ mastery of pedagogical theories in Teaching English for Young Learners (TEYL) courses. During the COVID-19 shift to remote teaching, TEYL teacher education faced the challenge of ensuring future teachers developed adequate pedagogical content knowledge despite reduced face-to-face interaction. This study addresses this gap by investigating the relationship between students’ perceptions of synchronous (Zoom) and asynchronous (Moodle) learning and their academic performance in TEYL course. Methodology: This quantitative ex post facto study involved 71 fifith-semester students enrolled in TEYL course, divided into a synchronous class (n=40) and an asynchronous class (n=31). Data were collected through a validated 34-item perception questionnaire (Cronbach’s α = 0.87) and midterm exam scores. While the sample size was relatively small, it provided initial evidence of how different modalities function in a teacher education context. Findings: Regression analysis revealed a significant positive relationship between students’ perceptions and their midterm exam scores in both modalities ((R² = .309 synchronous; R² = .325 asynchronous). However, independent t-test results showed no statistically significant difference in exam performance between the two groups (t(69) = 0.165, p = 0.87). Conclusion: These findings suggest that well-structured synchronous and asynchronoous learning can both support TEYL teacher education effectively, provided that instructional design aligns with students’ need and course objectives. Originality: This study is original in its focus on pre-service teachers in TEYL course an underexplored participant group and highlights how modality choice interacts with students’ perceptions to shape learning outcomes. Its findings offer practical insights for teacher educators designing blended or hybrid curricula in the post-pandemic era.